Inokulasi Mikrokapsul Bakteri Rizosfer Dari Tanah Erupsi Gunung Sinabung Sebagai Booster Pertumbuhan Bibit Kopi Robusta (Coffea canephora L.) - Tarigan, Rico Kris Hadinata; Warsito, Kabul; Setiawan, Andi (Mahesa Research Institute, 2025)
This study aims to evaluate the effect of rhizosphere bacteria microcapsule fertilizer application and chicken manure fertilizer on the growth of robusta coffee seedlings (Coffea canephora L.). The background of the study is based on the need for environmentally friendly superior coffee seedlings, considering that the continuous use of inorganic fertilizers has the potential to reduce soil fertility. Rhizosphere bacteria-based biofertilizers are expected to be able to increase plant growth organically, while microencapsulation technology is used to increase the effectiveness and resistance of bacteria in the environment. This study used a two-factorial Completely Randomized Design with 16 treatments and 5 replications, involving variations in the dose of chicken manure fertilizer (0, 100, 200, 300 grams) and rhizosphere bacteria microcapsules (0, 5, 7.5, 10 grams). The parameters observed included plant height, number of leaves, leaf area, stem diameter, and root length. The results showed that the application of rhizosphere bacteria microcapsules at a dose of 7.5 grams (M2) significantly increased the height of robusta coffee seedlings, while the dose of 300 grams of chicken manure fertilizer (K3) also had a significant effect on plant height growth. However, the treatment did not provide a significant difference in the number and area of leaves. This study concluded that the combination of rhizosphere bacteria microcapsules and chicken manure fertilizer can be an environmentally friendly solution to optimally increase the growth of robusta coffee seedlings